(untitled) (Journal of Plant Disease Sciences, 2018)
Ralstonia solanacearum, the causal organism of bacterial wilt of solanaceous crops is a major limitation on the production of brinjal. In vitro studies were carried out during Kharif, 2014 at Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani to find out the effectiveness of botanicals, bioagents and organic amendment to inhibit the growth of R. solanacearum. All the botanicals with different plant parts at 5, 10 and 20 per cent concentration and soil amendments at different levels of application evaluated in vitro (pot culture) against susceptible brinjal cv. Puneri Kateri Botanicals neem seed kernel extract, neem leaf extract and noni fruit extract @ 20% conc. recorded significantly highest reduction in mortality 60.48, 52.97 and 46.56 per cent, respectively and soil amendments viz., vermicompost (50 g/kg soil) and RDF/plant with gypsum levels (66 g and 50g/kg soil) recorded significantly highest reduction in mortality 63.40, 62.20 and 61.41 per cent, respectively.